E-learning Inequalities for Disabled Students in Bangladesh: Covid-19 Perspective (Social Science Review, 2023)
The education system is vital to eliminating societal inequalities. Internet-based learning systems launched in low- and middle-income countries by providing an equity vibe; however, Bangladesh's reality differs from this philosophy. Bangladesh adopted an e-learning strategy to perk up its literacy rate during the COVID-19 lockdown. However, the current situation has become complex due to insufficient internet network and technological setup, the market-generated welfare policy, little accountability of the state, and inadequate fund release to accommodate this new learning system. Disabled students got few benefits from the system; for instance, it reduced mobility crisis; hence financial, societal, and cultural blockades become uniquely problematic to some extent. The current article will analyse existing secondary literature to understand disabled students' academic future in Bangladesh, relevant policy, and practices to determine their citizenship rights.Social Science Review, Vol. 39(3), Dec 2022 Page 73-91